2021
DOI: 10.1093/bjsopen/zrab101
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in restorative versus non-restorative resections for rectal cancer: systematic review

Abstract: Background Low rectal cancers could be treated using restorative (anterior resection, AR) or non-restorative procedures with an end/permanent stoma (Hartmann’s, HE; or abdominoperineal excision, APE). Although the surgical choice is determined by tumour and patient factors, quality of life (QoL) will also influence the patient's future beyond cancer. This systematic review of the literature compared postoperative QoL between the restorative and non-restorative techniques using validated measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Sphincter-preserving surgical approaches to the treatment of low-rectal cancer clinical cases have been widely adopted to date, with recent studies having shown these approaches to be safe and effective [30,31], although the superiority to APR with respect to patient long-term quality of life is still controversial [32,33]. Advances in minimally invasive laparoscopic surgical techniques have Wexner Score RAS (n=169) 0 (0,0) 0 (0,1) 0 (0,1) 0 (0,0) LAS (n=404) 0 (0,0) [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphincter-preserving surgical approaches to the treatment of low-rectal cancer clinical cases have been widely adopted to date, with recent studies having shown these approaches to be safe and effective [30,31], although the superiority to APR with respect to patient long-term quality of life is still controversial [32,33]. Advances in minimally invasive laparoscopic surgical techniques have Wexner Score RAS (n=169) 0 (0,0) 0 (0,1) 0 (0,1) 0 (0,0) LAS (n=404) 0 (0,0) [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experienced research nurses or doctors interviewed patients with their consent to collect the results of questionnaires pertaining to postoperative urogenital and bowel function. The First Affiliated Hospital of Anhui Medical University ethics committee accepted this investigation, with all patient participants providing informed consent (Reference number: Quick-PJ 2021- [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Investigation Designmentioning
confidence: 99%
“…This is the first meta-analysis to specifically compare CAA and APR. While previous systematic reviews have addressed similar questions [31][32][33], this review included only studies defining low rectal cancer treated with coloanal anastomosis and excluding upper rectal cancer. Complete comparative data was required for meta-analysis.…”
Section: Ta B L E 2 Methods Of Coloanal Anastomosismentioning
confidence: 99%
“…Few studies have evaluated the comparative effectiveness of SPS with permanent stoma with respect to patient-reported outcomes (PROs). A systematic review which included nineteen studies with a total of 6453 patients concluded that it is not possible to draw a firm conclusion on postoperative QoL and body image following restorative versus non-restorative rectal cancer surgery ( 5 ).Post-treatment function and quality of life in patients with rectal cancer have been insufficiently studied ( 6 ).…”
Section: Introductionmentioning
confidence: 99%